Global brain asymmetry is increased in schizophrenia and related to avolition. (23rd March 2017) - Núñez, C.; Paipa, N.; Senior, C.; Coromina, M.; Siddi, S.; Ochoa, S.; Brébion, G.; Stephan‐Otto, C.
Abstract : Objective: Schizophrenia may be the result of a failure of the normal lateralization process of the brain. However, whole‐brain asymmetry has not been assessed up to date. Here, we propose a novel measure of global brain asymmetry based on the Dice coefficient to quantify similarity between brain hemispheres. Method: Global gray and white matter asymmetry was calculated from high‐resolution T1 structural images acquired from 24 patients with schizophrenia and 26 healthy controls, age‐ and sex‐matched. Some of the analyses were replicated in a much larger sample ( n = 759) obtained from open‐access online databases. Results: Patients with schizophrenia had more global gray matter asymmetry than controls. Additionally, increased gray matter asymmetry was associated with avolition, whereas the inverse relationship was found for anxiety at a trend level. These analyses were replicated in a larger sample and confirmed previous results. Conclusion: Our findings suggest that global gray matter asymmetry is related to the concept of developmental stability and is a useful indicator of perturbations during neurodevelopment.